Taxation and innovation: How R&D tax credit schemes foster innovation in the private sector - Oliver Falck; Anna Kerkhof; Christian Pfaffl (EconPol Forum, 2023)
Research and Development (R&D) is crucial to secure continued economic growth and prosperity. Private sector investments in R&D are typically too low, which constitutes a market failure. Governments use R&D tax credit schemes to compensate for this failure. Input-based tax credit schemes and lenient corporate taxation are especially useful to stimulate private sector R&D activities
Keywords: 330